(untitled) (Architecture Image Studies, 2026)
Money politics remains a persistent challenge to electoral democracy in Indonesia, particularly at the local level where political competition, socio-economic vulnerability, and weak law enforcement often intersect. This study aims to analyze the role of the police in supervising vote-buying practices by political parties in the 2024 legislative election in Maros Regency, with specific attention to inter-agency coordination within the Integrated Law Enforcement Center (Gakkumdu). Employing a qualitative case study approach, data were collected through in-depth interviews, non-participant observation, and document analysis involving the police, the General Elections Supervisory Agency (Bawaslu), the prosecutor’s office, political parties, and community representatives. The findings reveal that police involvement in vote-buying supervision is embedded within a collaborative institutional framework characterized by collective decision-making, formal and informal coordination, and preventive-oriented strategies. Preventive efforts, including legal socialization, political education, vulnerability mapping, joint patrols during the quiet period, and participatory supervision, play a central role in mitigating money politics. However, the study also identifies significant constraints, particularly difficulties in evidence collection, limited witness cooperation, and strict procedural time limits that hinder effective prosecution. This research concludes that while the Gakkumdu-based oversight model strengthens electoral supervision institutionally, enhancing legal certainty, witness protection, and investigative timeframes is essential to improve the effectiveness of law enforcement against money politics and safeguard democratic integrity at the local level.